(untitled) (Carte Romanze, 2025)
The paper analyzes the fortunes of Seneca’s traditions per excerpta in Florence between the late 14th and early 15th centuries. In particular, it focuses on the manuscript Florence, Biblioteca Riccardiana, 2618 (Florilegio Riccardiano), which contains an extensive florilegium of excerpts and proverbs from Senecan (or pseudo-Senecan works). Its contents are notable for the presence of a vernacular translation (volgarizzamento) per excerpta of the De clementia. It finds precise parallels in a second (and different) excerpted version, transmitted by the manuscript Florence, Biblioteca Riccardiana, 1691. The final section focuses instead on a manuscript (also composed of Senecan works) of great importance in 15th-century Florence (Florence, Biblioteca Nazionale Centrale, II.III.326), in which we have a series of unique translations of a wide constellation of Senecan texts (such as the De paupertate).